2014
DOI: 10.1111/joms.12098
|View full text |Cite
|
Sign up to set email alerts
|

A Balancing Act: Emotional Challenges in theHRRole

Abstract: Despite much academic work and the development of multiple typologies, we are still some way from understanding the HR role. There is a dearth of empirical evidence on HR professionals' work and recent models have been criticized for not adequately reflecting the challenges of trying to balance competing stakeholder interests. We approach this lacuna by focusing on an issue that has not been fully considered in relation to HR work – emotion. Drawing on the findings of a broader study into emotional labour, we … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
42
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(46 citation statements)
references
References 74 publications
(119 reference statements)
0
42
0
1
Order By: Relevance
“…The role that HR practitioners should play in organisations is the subject of an on-going debate (O'Brien & Linehan, 2014). In line with the early work of Ulrich (1997), many scholars advocate that HR practitioners should be allowed to play a more strategic role in organisations (see De Nisi, Wilson & Biteman, 2014;Sikora & Ferris, 2014).…”
Section: Introductionmentioning
confidence: 94%
See 1 more Smart Citation
“…The role that HR practitioners should play in organisations is the subject of an on-going debate (O'Brien & Linehan, 2014). In line with the early work of Ulrich (1997), many scholars advocate that HR practitioners should be allowed to play a more strategic role in organisations (see De Nisi, Wilson & Biteman, 2014;Sikora & Ferris, 2014).…”
Section: Introductionmentioning
confidence: 94%
“…Given the current criticisms surrounding the HR function, research should focus on exploring the underpinning competencies that are the building blocks of effective HR practices (Abdullah, 2014). The lack of detailed empirical research on HR competencies and functions is widely recognised (Abdullah, 2014;Abdullah, Musa & Ali, 2011;O'Brien & Linehan, 2014). The main objective of this research was to explore the extent to which HR practitioners are currently allowed to display HR competencies in the workplace and whether any significant differences exist between perceived HR competencies, based on the respondents' demographic characteristics.…”
Section: Purposementioning
confidence: 99%
“…It can also be suggested that the grounded theory approach has its critics and is known to have a number of limitations (Suddaby, 2006;Urquhart, Lehmann & Myers, 2010), however, the grounded theory approach is recognized as an interpretive process, contributes to the development of theory (Urquhart, Lehmann & Myers, 2010), and allows the researcher a certain degree of flexibility (O'Brien & Linehan, 2014). What is encouraging is that several areas for further research emerged from the study and we suggest that work in the area of reducing cultural distance can be undertaken in order to explain how specific aspects of marketing can be improved through information sharing involving in-house groups (interpreted as intra-group activity) and partnership arrangements (interpreted as inter-group activity).…”
Section: Limitations and Research Implicationsmentioning
confidence: 99%
“…While there has been considerable interest to demarcate HR roles, this has largely involved theoretical debates and prescriptive models, rather than empirical investigation of how HR roles are enacted (O'Brien and Linehan, 2014;Pritchard, 2010;Stiles and Trevor, 2006). The extant literature has largely centred on the domestic context (e.g.…”
Section: Cct Provision and Hr Rolesmentioning
confidence: 99%
“…Conner and Ulrich, 1996;Storey, 1992;Ulrich, 1997;Ulrich and Brockback, 2005). There is, however, a dearth of empirical studies into how HR professionals' enact their roles (O'Brien and Linehan, 2014;Pritchard, 2010;Stiles and Trevor, 2006), in particular in international settings (Welch and Welch, 2012) and in relation to specific issues, such as CCT. In light of empirical evidence that ‗personnel managers will have different roles in relation to different issues with which they are concerned ' (Procter andCurrie, 1999: 1078), a more fine grained exploration of specific HR roles in international settings is called for.…”
mentioning
confidence: 99%